A quantitative analysis of factors influencing housing demand in SA - Chipswa, Isaac (Research of GSB, 2017)
After the 2008 financial crisis, which was heavily influenced by the housing market bubble, studying the housing market has become a subject of major interest to many scholars and investors globally. Literature identifies several key factors that influence housing demand including, employment, income levels, gross domestic product, monetary policy and demographics among others. This thesis investigates the factors that influence housing demand in South Africa and incorporates quantitative analysis on the relationship between interest rates, exchange rates, inflation and housing demand. Most studies on this subject have been conducted in the developed market context, as such, this research study aims to fill the gap and influence future thinking in the emerging market context. There is currently limited research on the relationship between interest rates, exchange rates, inflation in relation to housing demand in the developing world including South Africa. In the analysis, housing demand is measured by mortgage loans disbursed monthly by the top four commercial banks in South Africa. In addition to desktop research, the research also incorporates perspectives and thinking from some of the renowned professionals and academics in the housing market. Monthly time series data (from 1995 up to 2015) on interest rates, exchange rates, inflation (CPI) and mortgage loans disbursed was obtained from the South African Reserve Bank (SARB) website. Based on multiple regression analysis, the output results are in line with views held by most academics in the literature review. It was observed from the results that the housing demand (as measured by the mortgage loans disbursed to individuals) is negatively correlated to prime overdraft/ inflation rate and positively correlated to foreign exchange rate. As such, an increase in interest and inflation rates, result in a decrease in housing demand. An increase in exchange rate results in decreased housing demand.